Analisis UU ITE Terhadap Hak Digital dan Nilai-Nilai Demokrasi di Indonesia - Afisa, Afisa; Qodir, Zuly; Habibullah, Akhmad; Sugiharto, Unggul (The Journal of Society and Media, 2024)
This article aims to analyze through online mass media critically and case studies the dual nature of the passage of the Electronic Information and Transaction Law (ITE Law) as an instrument of digital rights protection and a potential threat to freedom of expression and democratic values in Indonesia. This research uses a descriptive-qualitative method to analyze data from 2020 to 2022 with NVivo 12 Plus, referencing Mazmanian and Sabatier's (1983) theory of policy implementation effectiveness. It focuses on the willingness of target groups to comply with policy outputs and the actual impact of those outputs.. Third, fundamental improvements to the law. Research shows that community compliance with the ITE Law has increased, evidenced by a decrease in cases from 2020–2022. The indicator of the Real Impact of Policy Outputs shows that the public and activists oppose implementing the ITE Law because freedom of expression is restricted. Then the indicator of fundamental improvement of the law is that the government will revise the articles of the ITE Law, especially articles 27, 28, and 29, which are considered multi-interpretive.